Automated Compounding of Parenteral Nutrition for Pediatric Patients: Characterization of Workload and Costs - Raimbault, Mélina (Pediatric Pharmacy Advocacy Group, 2012)
OBJECTIVES: Parenteral nutrition (PN) compounding in large hospital centers is now largely automated using volumetric pump systems. No study has examined the pharmacy workload and costs associated with this process. This study was designed to characterize these elements at our center and to identify areas for potential improvement. METHODS: We retrospectively analyzed all PN orders compounded from May 19, 2007, to June 25, 2010. Patients were divided into groups according to the ward where PN was initiated. RESULTS: The age and weight of patients at initiation of PN were similar throughout the study, except in neonatology, where initiation now occurs earlier in life (age 1.3 ± 2.7 days in 2010 vs. 3.4 ± 9.4 in 2007; p=0.003). An average of 894 orders per month were compounded. A total of 59% of orders were for neonatal patients. The average cost of source solutions per PN order increased from Can$23.27 in 2007 to Can$37.78 in 2010. Partially used source solutions discarded at the end of the day represented between 7.7% and 9.2% of total source solution cost. Amino acids in 3-L bags were responsible for the largest waste, with Can$953 to Can$1048 wasted monthly. CONCLUSIONS: PN compounding at our center represents an important workload and increasing costs. A reduction in source solution waste, for example, by reducing the use of large source solution containers, would be beneficial.